2014
DOI: 10.1080/19415257.2014.886282
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood teachers’ perceived competence during transition from teacher education to work: results from a longitudinal study

Abstract: The transition from education to work is a challenge for early childhood teachers. In this study, competence self-ratings of 348 German early childhood teachers were investigated one year before, at the end of and four months after early childhood teacher education at universities and vocational schools. Perceived competence was assessed by means of a questionnaire. Invariant from time of measurement, confirmatory factor analysis yielded one factor with child-related competences and one factor with environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 85 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Sang et al (2010) even referred specifically to TSE with computers. Malinen (2013) identified efficacy domains of inclusive instruction, collaboration, and managing behavior; Yin et al (2013) identified efficacy domains in relation to professional growth, participation in decision making, and perceived impact on colleagues; and Mischo (2015) identified a range of activities that he categorized as either child-related competencies or environment-related competencies. Although some of these domains overlap each other and with the domains represented by the TSES, the recommendation made more than 10 years ago by Poulou (2007, p. 214) that "future research should encompass additional dimensions of teaching efficacy in order to reflect the multidimensionality and complexity of teaching" continues to resonate.…”
Section: Insights About Construct Conception and Coveragementioning
confidence: 99%
“…Sang et al (2010) even referred specifically to TSE with computers. Malinen (2013) identified efficacy domains of inclusive instruction, collaboration, and managing behavior; Yin et al (2013) identified efficacy domains in relation to professional growth, participation in decision making, and perceived impact on colleagues; and Mischo (2015) identified a range of activities that he categorized as either child-related competencies or environment-related competencies. Although some of these domains overlap each other and with the domains represented by the TSES, the recommendation made more than 10 years ago by Poulou (2007, p. 214) that "future research should encompass additional dimensions of teaching efficacy in order to reflect the multidimensionality and complexity of teaching" continues to resonate.…”
Section: Insights About Construct Conception and Coveragementioning
confidence: 99%
“…Further, preservice training is assumed to ensure that practitioners have the competencies needed to support the development and learning of young children, laying a foundation for teachers' PD (Hamre 2014;Institute of Medicine and National Research Council 2015). In recent studies, surveys have been used to investigate prospective ECEC teachers' self-esteem (e.g., Mischo 2015), teacher beliefs (e.g., Vartuli and Rohs 2009), self-efficacy (e.g., Guo et al 2010), and self-reported perceptions of their professional competence (e.g., Mischo 2015;Strohmer and Mischo 2016). Observational studies of prospective teachers are needed, however, to provide direct insight into pre-service teachers' interaction skills in ECEC practice.…”
mentioning
confidence: 99%